Exosomal lncRNA LINC01356 Derived From Brain Metastatic Nonsmall-Cell Lung Cancer Cells Remodels the Blood–Brain Barrier - Geng, Sumin; Tu, Shaohua; Bai, Zhenwei; Geng, Yixiong (Frontiers in Oncology, 2022)
Brain metastasis is a severe complication that affects the survival of lung cancer patients. However, the mechanism of brain metastasis in lung cancer remains unclear. In this study, we constructed an in vitro BBB model and found that cells from the high-metastatic nonsmall cell lung cancer (NSCLC) cell line H1299 showed a higher capacity to pass through the blood–brain barrier (BBB), as verified by Transwell assays, than cells from the low-metastatic NSCLC cell line A549. Brain microvascular endothelial cells (BMECs) could internalize H1299-derived exosomes, which remarkably promoted A549 cells across the BBB. The BBB-associated exosomal long noncoding RNA (lncRNA) was selected from the RNA-Seq dataset (GSE126548) and verified by real-time PCR and Transwell assays. LncRNA LINC01356 was significantly upregulated in H1299 cells and exosomes derived from these cells compared to that of A549 cells. Moreover, LINC01356 was also upregulated in serum exosomes of patients with NSCLC with brain metastasis compared with those without metastasis. In addition, BMECs treated with LINC01356-deprived exosomes expressed higher junction proteins than those treated with the control exosomes, and silencing LINC01356 in exosomes derived from H1299 cells could inhibit A549 cells from crossing the BBB. These data might indicate that the exosomal lncRNA LINC01356 derived from brain metastatic NSCLC cells plays a key role in remodeling the BBB system, thereby participating in brain metastasis in lung cancer.